Testimonies of War during Cuba’s Fight for Independence (1868-1898) - Jorge Camacho (Journal of Global Initiatives, 2020)
In October 1868, a group of Cuban rebels from the Province of Bayamo took arms against the Spanish regime starting a war that lasted 10 years, at which point the Spanish government and the rebels reached a pact that put an end to the hostilities. As a result of this pact, Cubans were allowed to form new political parties, create newspapers that supported their “autonomistas” political views, and in 1886 the Spanish government finally abolished slavery in its entirety, putting an end to an institution that was already widely criticized. During this time of peace, due to the shortage of men caused by the war in the labor market, Cuban women started occupying positions in factories, published in newspapers, and were able to attend middle and higher education, which raised their educational levels considerably. In this article I will analyze some testimonios of the Cuban War of Independence, some literary and some written by participants, that show how by the middle of 1880s Cubans had started reflecting on the war itself, the different groups that had intervened in the conflict, and what, if any, purpose the conflict had served.